Photoelectrochemical and photoresponsive properties of Bi2s3 nanotube and nanoparticle thin films - Tahir, A.A.; Ehsan, M.A.; Mazhar, M.; Wijayantha, K.G.U.; Zeller, M.; Hunter, A.D. (American Chemical Society, 2010)
Bi2S3 nanotubes and nanoparticle in the form of thin films were deposited on fluorine doped SnO2 (FTO) coated conducting glass substrates by Aerosol Assisted Chemical Vapor Deposition (AACVD) using tris-(N,N-diethyldithiocarbamato)bismuth(III), [Bi(S2CN(C2H5)(2))(3)](2) (1) as A precursor. Thin films were deposited from solutions of (1) in either chloroform, dichloromethane, or a 1:1 mixture of chloroform and toluene at temperature between 350 to 450 degrees C and characterized by X-ray diffraction (XRD), UV-vis spectroscopy, field emission gun scanning electron microscopy (FEGSEM), and energy dispersive X-ray (EDX) analysis. FEGSEM images of films deposited from chloroform or dichloromethane exhibit well-defined and evenly distributed nanotubes with an average internal diameter of 40 nm. Films deposited from chloroform/toluene, on the other hand, have compact nanostuctured morphology. Bandgaps of 1.85 and 1.8 eV were estimated for nanotubes and nanoparticles, respectively, by extrapolating the linear part of the Tauc plot recorded for the films. The n-type Bi2S3 thin films display a reasonable photoactivity under illumination and are thus promising candidates for photoelectrochemical applications. The photoelectrochemical characteristics recorded under AM 1.5 illumination indicated photocurrent density of 1.9 mA/cm(2) and 1.0 mA/cm(2) at 0.23 V versus Ag/AgCl/3 M KCl for the films deposited from chloroform and chloroform/toluene, respectively. The photocurrent is among the highest reported for any Bi2S3 photoelectrode to date. Repeated illumination cycles show that the Bi2S3 thin films display a reasonable photosensitivity and response indicating their potential to be used in photodetector and optoelectronic nanodevice applications.